Terminologia, tradução e linguística de Córpus: análise de uma obra de ficção científica cyberpunk - Araújo, Soraya Amaral de (2023)
Science fiction has produced over the years a variety of subgenres. Our corpus study is based on science fiction's cyberpunk subgenre which focuses on a ‘high tech, low life’ theme. The term cyberpunk is a combination of cybernetics and punk culture, featuring settings of advanced technologies, alternative virtual realities, artificial intelligence, and cyberspace in a degraded and dystopian social background. This context has proven conducive to the observation of contemporary linguistic phenomena associated with the increasing popularization of scientific and technical domains and the need for effective communication in different specialized areas, which includes the development of updated terminology and specialized languages created to fulfill the various communicative functions of our time, including how the employed terminology is translated. Some studies suggest that this development can be extrapolated to the realm of fictional narratives in their several forms of artistic expression, particularly in science fiction, which features, among its characteristics, the use of terminology from different fields of knowledge, lending verisimilitude and coherence to the literary genre within the universe of discourse in which it is presented. The aim of this work with a cyberpunk science fiction corpus is, therefore, to use Corpus Linguistics resources to identify the terminology used in the corpus of study according to their related fields of knowledge, and to analyze and describe the translation modalities used in transposing this terminology as an important component for understanding this linguistic phenomenon expressed in the original English text and its translation into Brazilian Portuguese in Richard Morgan's novel Altered Carbon, translated by Edmo Suassuna as Carbono Alterado. To achieve this, we explore the potential of interdisciplinary theoretical-methodological relationships integrated by the studies of Terminology, Translation, and Corpus Linguistics, seeking to ground, identify, analyze, and describe the terminology developed by the author in the contexts in which they appear, as well as their translations, and in some way, contribute to the interest and expansion of these subjects. Once carried out, the work points out to a satisfactory performance of the method used, as it has integrated a diversity of accessible and useful tools and produced quantifiable and interpretable data. The analysis of terminology carried out through translation modalities has indicated the predominant presence of direct translation modalities, at the same time as it revealed some particularities related to the corpus of study and the universe of ethnoliterary discourse in science fiction.